2016
DOI: 10.1186/s12913-016-1757-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture and associated factors: A quantitative and qualitative study of healthcare workers’ view in Jimma zone Hospitals, Southwest Ethiopia

Abstract: BackgroundPatient safety culture is an important aspect for quality healthcare delivery and is an issue of high concern globally. In Ethiopia health system little is known and information is limited in scope about patient safety culture. Therefore, the aim of this study was to assess the level of patient safety culture and associated factors in Jimma zone Hospitals, southwest Ethiopia.MethodsFacility based cross sectional quantitative study triangulated with qualitative approaches was employed from March to Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
97
7
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(144 citation statements)
references
References 25 publications
19
97
7
6
Order By: Relevance
“…The results revealed that nursing students have attained a relatively modest level of perspective on training hospitals' infection prevention climate (M = 3.32, SD = 0.62). This result was in accordance with a study conducted in China , Ethiopia (Wami et al, 2016), and India (Sodhi et al, 2013). However, this result was lower than that conducted among nurses in Saudi Arabia (M = 3.86, SD = 0.51) (Colet et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The results revealed that nursing students have attained a relatively modest level of perspective on training hospitals' infection prevention climate (M = 3.32, SD = 0.62). This result was in accordance with a study conducted in China , Ethiopia (Wami et al, 2016), and India (Sodhi et al, 2013). However, this result was lower than that conducted among nurses in Saudi Arabia (M = 3.86, SD = 0.51) (Colet et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The present study investigated the current status of patient safety culture in Ethiopian public hospitals using the HSOPSC instrument. The results of this study revealed that the overall positive response rate for all dimensions of the HSOPSC survey was not satisfactorily enough, akin to the findings from another local study [23]. Wami et al [23] assessed the patient safety culture in Jimma Zone (Oromia region) and have found that the overall mean score for the positive perception of patient safety culture dimension was 46.7%.…”
Section: Discussionmentioning
confidence: 73%
“…The results of this study revealed that the overall positive response rate for all dimensions of the HSOPSC survey was not satisfactorily enough, akin to the findings from another local study [23]. Wami et al [23] assessed the patient safety culture in Jimma Zone (Oromia region) and have found that the overall mean score for the positive perception of patient safety culture dimension was 46.7%. However, our study scored lower results when compared with the findings from other low-and middle-income countries (e.g.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…2,3 Studies [4][5][6] show that the improvement in the quality of medical care and patient safety is closely related to a patient's consciousness of a good culture, and a positive safety culture can promote patient safety, can increase the satisfaction of patients about the hospital and can improve the patient's medical experience. 7,8 To date, many countries have initiated patient safety culture research, 9,10 especially developed countries. 8,[11][12][13] Some scales have been designed, 2 such as the Patient Safety Climate in Healthcare Organizations (PSCHO) in America, which evaluates the status of the patient safety culture in medical institutions.…”
Section: Introductionmentioning
confidence: 99%